Model of trauma-induced coagulopathy including hemodilution, fibrinolysis, acidosis, and hypothermia: Impact on blood coagulation and platelet function. Issue 2 (February 2017) - Shenkman, Boris; Budnik, Ivan; Einav, Yulia; Hauschner, Hagit; Andrejchin, Mykhaylo; Martinowitz, Uriel
Abstract : BACKGROUND: Trauma-induced coagulopathy (TIC) is commonly seen among patients with severe injury. The dynamic process of TIC is characterized by variability of the features of the disease. METHODS: A model of TIC was created. Hemodilution was produced by mixing the blood with 40% Tris/saline solution, fibrinolysis by treating the blood with 160 ng/mL tPA, acidosis by adding 1.2 mg/mL lactic acid achieving pH 7.0 to 7.1, and hypothermia by running the assay at 31°C. Intact blood tested at 37°C served as control. Clot formation was evaluated using rotation thromboelastometry. Platelet adhesion and aggregation were assayed at a shear rate of 1800 s −1 using Impact-R device. RESULTS: Clotting time was not affected by any of the TIC constituents used. Clotting initiation was reduced by hemodilution and further reduced by additive hypothermia. The propagation phase of blood clotting was reduced by hemodilution, further reduced by additive hypothermia, and maximally reduced if additionally combined with fibrinolysis. No effect of fibrinolysis on clot propagation was observed at 37°C. Maximum clot firmness was reduced by hemodilution, further reduced by additive fibrinolysis, and maximally reduced if additionally combined with hypothermia. No effect of hypothermia on clot strength was observed in the absence of fibrinolysis. Platelet adhesion (percentage of surface coverage) and aggregation (aggregate size) under flow condition were reduced by hemodilution and further reduced by additive acidosis. Introduction of tPA to diluted blood had no effect on platelet function. CONCLUSION: The study revealed a differential effect of TIC constituents—hemodilution, hypothermia, fibrinolysis, and acidosis—on clot formation and platelet function. The effect of one factor may influence that of another factor. These data may be helpful to better understand the pathogenesis of TIC and to elaborate an individually tailored treatment strategy. LEVEL Of EVIDENCE: A new model of TIC is created. Contribution of various constituents to pathogenesis of TIC and their interactions are evaluated.